H. Mukhtar Muda Nasution 1921-2009: Sejarah dan Kontribusi - Siregar, Masnuripa; Nasution, Abdul Ghani Jamora; Putri, Cahya Widya; Panjaitan, Suci Mawar Syahraini; Permatasari, Lutfia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sheikh H. Mukhtar Muda Nasution, with his nickname Marahadam Nasution, was a cleric who persistently fought to advance Islamic education in Barumun District, Padang Lawas Regency. In order to fulfill his desire to deepen religious knowledge he also studied in the holy land of Mecca for 4 years, besides studying he was trusted to teach at Madrasah Nahdlatul Ulama Sibuhuan which has now changed its name to Madrasah Tsanawiyah Aek Hayuara in Sibuhuan for 9 years, this was the beginning of his journey. In advancing Islamic education, he did many things to realize these ideals, including building several formal educational institutions in Sibuhuan, Barumun District. The aim of this research is to describe H. Mukhtar Muda Nasution 1921-2009 History and Contributions. This research uses a qualitative approach with a literature study method by collecting relevant data and analyzing and studying it in detail and in depth, as well as holding discussions to discuss the context related to the material in the journal. From this research, 2 (two) results were found, namely (1) Contribution of H. Mukhtar Muda Nasution in building many fast schools, namely the Aek Haruaya Sibuhuan Islamic boarding school (2) and biography of Sheikh H. Mukhtar Muda Nasution in developing the Islamic religion.